IDENTIFYING THE DEPENDENCIES BETWEEN IT PROJECT CONTEXT AND BUSINESS ANALYSIS DOCUMENT CONTENT - Denys Gobov; Oleksandra Zuieva (Сучасний стан наукових досліджень та технологій в промисловості, 2023)
The subject matter of the article is software requirements documentation practices in IT projects. The goal of the work is to identify what information is included in business analysis deliverables and how the project context influences the content of business analysis documents. The following tasks were solved in the article: to examine the industrial standards and experience of business analysts and requirements engineers in requirements specification and modeling activities in software development, to create and conduct a survey on practices in requirement documentation activities in IT projects, to define practitioners’ preferences regarding business analysis documents’ content, and to define how project context influences document content. The following methods are used: three hundred and twenty-four practitioners from Ukrainian companies were surveyed about their current preferences in business analysis document creation, their experience, and project profile attributes in which techniques were used. The Chi-Square test of independence and Cramer’s V effect size measure were applied to define statistically significant dependencies between project context and business analysis document content. The following results were obtained: a list of the most commonly used elements in business analysis documents was defined. Seventy-eight statistically significant associations for pairs "project context – business analysis document content" were found based on the p-value of the Chi-Square test, for eighteen of which the significance of the identified dependencies was confirmed using the Cramer’s V effect size measure. Conclusions: It is concluded that project context influences the content of business analysis documents in IT projects. The most influential factors are the business analyst’s experience, team distribution, company size and type, template usage, and the purpose of using the requirements documents. The found dependencies can guide the selection of business analysis document structure and the creation of project-specific templates during the creation business analysis approach and business analysis information management approach.